Optimization of Culture Conditions for Production of β-Mannanase by Strain Nonomuraea sp. ID06-379 using Submerged Substrate Fermentation - Ratnakomala, Shanti; Yopi, Yopi; Suhartono, Maggy Thenawidjaja; Meryandini, Anja; Prasetya, Bambang (Annales Bogorienses, 2025)
The objective of this study was to investigate the effect of media compositions on the production of β-mannanase by Nonomuraea sp. ID06-379. The study was focused on the influence of carbon, nitrogen, phosphorus and detergents on β-mannanase synthesis through manipulating media compositions on production medium. The results indicated that for carbon sources, locus bean gum (0.745 ± 0.036 U/ml) showed maximum mannanase activity. Malt extract was the best nitrogen source for producing β-mannanase (1.075 ± 0.006 U/ml), (NH4)2HPO4 as phosphate source (1.733 ± 0.026 U/ml) and Tween 80 (1.145 ± 0.003 U/ml) as surfactants effect on increasing permeability of bacterial cell membrane, enhancing membrane transport and excretion of extracellular enzymes into the production media. The results showed that 1% malt extract, 0.5% locus bean gum and 0.05% (NH4)2HPO4 were good substances for nitrogen source, carbon source and phosphate respectively. The highest production of β-mannanase by Nonomuraea sp. ID06-379 (5.33 U/mg) was reached in the medium optimization (Vogel’s minimal medium) contained the following ingredients: 0.5% locus bean gum, 1% malt extract and 0.05% (NH4)2HPO4, under submerged fermentation with shaking at 120 rpm and 28C for 2 days incubation.